2022
DOI: 10.3389/fimmu.2022.875689
|View full text |Cite
|
Sign up to set email alerts
|

Immune Response of the Monocytic Cell Line THP-1 Against Six Aeromonas spp.

Abstract: Aeromonas are autochthonous bacteria of aquatic environments that are considered to be emerging pathogens to humans, producing diarrhea, bacteremia, and wound infections. Genetic identification shows that 95.4% of the strains associated with clinical cases correspond to the species Aeromonas caviae (37.26%), Aeromonas dhakensis (23.49%), Aeromonas veronii (21.54%), and Aeromonas hydrophila (13.07%). However, few studies have investigated the human immune response against some Aeromonas spp. such as A. hydrophi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 70 publications
2
15
0
Order By: Relevance
“…As for infections in professional phagocytic cells, a recent paper by Fernández-Bravo and Figueras performed infections of different Aeromonas species in the monocytic human cell line THP-1 [ 48 ]. Regarding infections in phagocytes, these authors also measured cell damage in relation to LDH release in infected cultures.…”
Section: Discussionmentioning
confidence: 99%
“…As for infections in professional phagocytic cells, a recent paper by Fernández-Bravo and Figueras performed infections of different Aeromonas species in the monocytic human cell line THP-1 [ 48 ]. Regarding infections in phagocytes, these authors also measured cell damage in relation to LDH release in infected cultures.…”
Section: Discussionmentioning
confidence: 99%
“…Fernández-Bravo et al. reported that A. dhakensis induced the overexpression of TNF-α together with a variety of immune-related genes, which might in turn be responsible for moderating the overwhelming type 2 immune response, re-establishing the type 1/type 2 immune balance ( 51 ). Some studies have shown that Salmonella enterica and Salmonella -based oral multiantigen DNA vaccines could result in a shift towards type 1 immune responses, as well as the presence of high levels of IgA in the nasal mucosa ( 52 , 53 ).…”
Section: Discussionmentioning
confidence: 99%
“…Before the infection, bacteria were grown at 37°C in serum and antibiotic-free DMEM under shaking conditions (100 rpm) for 24 h. Cell line J774A.1 was infected with the individual strains of A. caviae and Y. enterocolitica using overnight cultures at multiplicity of infection (MOI) of 10, i.e., the ratio between the number of bacteria and the number of targeted cells ( Fernández-Bravo and Figueras, 2022 ). For the polymicrobial studies, the bacterial strains were mixed in a ratio 1:1 and the cells were infected at MOI 10.…”
Section: Methodsmentioning
confidence: 99%
“…After infection with the single and the mixed strains at MOI 10, supernatants were collected at 4 h and 6 h post-infection ( Fernández-Bravo and Figueras, 2022 ). Cell damage was determined by measuring the lactate dehydrogenase (LDH) enzyme released into the supernatants, indicating plasma membrane damage.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation